Application of Health Education and Pappasang to Optimize the Psychosocial Development of Adolescents Engaged in Online Gaming - Boby Nurmagandi; Risna Damayanti (Institut Citra Internasional, 2025)
Excessive online gaming among adolescents can lead to the development of addiction, which is often compounded by psychosocial problems such as depression and anxiety. To address these concerns, interventions aimed at improving psychosocial development especially in areas related to behavior, peer groups, and extracurricular activities can be implemented through health education and the pappasang approach. The purpose of this study is to examine the impact of health education and pappasang in improving the psychosocial development of adolescents, to prevent online gaming addiction. This research employed a quasi-experimental design with a pre-post test and a control group. The sample for this study consisted of 57 respondents. The sample for this study was determined using total sampling. The instrument used to assess psychosocial development was the Strength And Difficulties Questionnaire (SDQ). The results of the study indicated that the implementation of health education and pappasang was effective in improving adolescent peer group dynamics within the intervention group, with a p-value of 0.001, which is less than the 0.05 significance threshold. Additionally, the intervention was effective in addressing hyperactivity, it was effective after therapy, with a p-value of 0.014, which is also less than 0.05. Furthermore, the intervention effectively improved the behavioral aspect after treatment, with a p-value of 0.014, again meeting the significance criteria. In conclusion, the application of health education and pappasang was found to be effective in improving the psychosocial development of adolescents who engage in online games.